Chromium(VI) biosorption studies using non-living microorganisms - Abdullah, Nur Humara' Lau (2006)
Chromium especially chromium (VI) species is a well-known toxic heavymetal for biological systems and is known to be a human carcinogen. However, hard chromium plating which uses chromium (VI) solutions is still the preferred method due to the higher deposition rates and ability to produce thick coatings. Thus the high concentration of chromium (VI) in chromium electroplating wastewater needs to be removed before being discharged. Due to the disadvantages and limitations of conventional techniques, particular attention is paid to the use of biological systems for heavy-metal removal from industrial wastewater. In this study, indigenous microorganisms in local textile wastewater were isolated and investigated for their chromium (VI) uptake in both simulated and real chromium electroplating wastewater. Preliminary studies showed that among the three bacteria: Acinetobacter calcoaceticus genospecies 3, Clavibacter agropyri and Cellulosimicrobium cellulans, Acinetobacter calcoaceticus genospecies 3 showed the highest chromium (VI) uptake at pH 8 with optimum biomass dosage of 0.75% and contact time of 120 hours. Acetic acid-pretreatment of this bacterial biomass was found to reduce chromium (VI) uptake. Chromium (VI) adsorbed on untreated biomass of Acinetobacter calcoaceticus genospecies 3 was suggested to occur as a multilayer based on the Brunauer, Emmett and Teller isotherm. The results from Transmission Electron Microscopy and infrared spectroscopy confirmed the involvement of amines, phosphate and carboxylate in surface adsorption of the metal with minor intracellular accumulation. Upon interaction with chromium electroplating wastewater, this bacterial biomass showed chromium (VI) uptake of 3.82 Â± 0.31 and 3.29 Â± 0.67 mg/g at acidic (3.75) and alkaline (8.08) pH rescpectively. However, this bacterial biomass could not reduce the chromium (VI) concentration to the legal limits